2016
DOI: 10.1038/srep35813
|View full text |Cite
|
Sign up to set email alerts
|

A role for intestinal TLR4-driven inflammatory response during activity-based anorexia

Abstract: Anorexia nervosa (AN) is associated with low-grade systemic inflammation and altered gut microbiota. However, the molecular origin of the inflammation remains unknown. Toll-like receptors are key regulators of innate immune response and their activation seems also to be involved in the control of food intake. We used activity-based anorexia (ABA) model to investigate the role of TLR4 and its contribution in anorexia-associated low-grade inflammation. Here, we found that ABA affected early the intestinal inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 50 publications
4
47
1
2
Order By: Relevance
“…ABA Procedure : Female 8‐week‐old C57BL/6 mice (Janvier Labs, Le Genest St Isle, France) were acclimatized 1 week at 23 °C with a reversed 12‐hour light‐dark cycle (dark phase: 10:30 a.m.–10:30 p.m.) and then were randomized into three groups as previously described . Briefly, the ABA model mice ( n = 16) were placed in cages with an activity wheel connected to Running Wheel software (Intellibio, Seichamps, France), while both limited‐food access mice (LFA, n = 16) and ad libitum mice (Control, n = 16) were placed in standard cages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA Procedure : Female 8‐week‐old C57BL/6 mice (Janvier Labs, Le Genest St Isle, France) were acclimatized 1 week at 23 °C with a reversed 12‐hour light‐dark cycle (dark phase: 10:30 a.m.–10:30 p.m.) and then were randomized into three groups as previously described . Briefly, the ABA model mice ( n = 16) were placed in cages with an activity wheel connected to Running Wheel software (Intellibio, Seichamps, France), while both limited‐food access mice (LFA, n = 16) and ad libitum mice (Control, n = 16) were placed in standard cages.…”
Section: Methodsmentioning
confidence: 99%
“…Undernutrition, dysbiosis, alteration of gut barrier function, stress, and inflammatory response are multiple factors that could be involved in the occurrence of associated intestinal disorders. Recently, by using the activity‐based anorexia (ABA) model mimicking restrictive anorexia and long‐term body weight loss, we reported an increased colonic permeability associated with decreased colonic protein content and TLR4 activation leading to an inflammatory response . It is well established that AN patients exhibit altered microbiota, as also observed during the ABA model .…”
Section: Introductionmentioning
confidence: 92%
“…Female 8‐week‐old C57BL/6 mice (Janvier Labs, Le Genest St Isle, France) were acclimatized 1 week at 23°C with a reversed 12‐hour light‐dark cycle (dark phase: 10:30 am – 10:30 pm ). ABA procedure was performed as previously described . Briefly, mice were randomized into 3 groups: activity‐based anorexia model mice (ABA) were placed in cages with an activity wheel connected to Running Wheel ® software (Intellibio, Seichamps, France), while both limited food access mice (LFA) and ad libitum mice (Control) were placed in standard cages.…”
Section: Methodsmentioning
confidence: 99%
“…Activity‐based anorexia (ABA) model is frequently used to study the pathophysiology of AN. ABA model has been initially developed in rats and then adapted in mice, with a progressive decrease of time access to food allowing long‐term study . ABA exhibited disturbed behavior, changes in central nervous system, and peripheral changes, ie, gut dysbiosis .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TLR4 signaling in immune cells plays a crucial role in maintaining chronic inflammatory state via producing inflammatory cytokines [11]. Several studies from animal models have showed that tissue inflammation correlating with IL-1, IL-6, and IL-17 expression is mediated by TLR4 signaling in chronic inflammatory diseases [12]. Recent studies found that an imbalance in T cell subsets, such as Th1, Th17, T regulatory cells, and the resulting altered profile of cytokine secretion from these cells, affects the susceptibility of CD [13].…”
Section: Introductionmentioning
confidence: 99%